Análise e avaliação das questões dos níveis 1 e 2 da primeira fase da obmep sob uma perspectiva de resolução de problemas - Silva, Paulo Henrique das Chagas (2017)
The Brazilian Mathematics Olympiads of public schools (OBMEP) has been established as one of the most important public policies of Basic Education, being present in almost one hundred percent of the Brazilian municipalities - reaching its apex in 2010, with a participation of 19,665,928 students, becoming the largest mathematical olympiad in the world - it acts directly in the education system and influences large-scale assessments, as it is the case with the Prova Brasil, supporting indicators such as the IDEB. With a proposal based on the development of students' taste for learning in Mathematics and the search for young talents, this Olympiad is a fertile field for putting into practice the studies and techniques of problem solving. The heuristic method or Polya method for solving problems is an important didactic / methodological strategy for the student's intellectual development and for teaching mathematics. In this regard, it is relevant to understand how OBMEP can be worked through from a problem-solving perspective, as well as to evaluate if it has fulfilled its role and if the points presented there fit the level of the students. This work is mainly based on the productions of George Polya (1995) for problem solving methods and on the first two parameters of the Classical Theory of Tests (CTT), to survey the research. The methodology used in this dissertation includes analysis of data and content. This study was made considering a sample of 184 students from the sixth to ninth grade of a public school in an inner city of the State of Rio Grande do Norte, and deals with the analysis of the First Phase of the OBMEP of 2016, in Levels 1 and 2. Throughout the same, it was realized that OBMEP's First Phase needs to be rethought, especially regarding to its level of difficulty, since there are issues that need to be more accessible to the students levels